53BP1 Deficiency Promotes Pathological Neovascularization in Proliferative Retinopathy - Troullinaki, Maria; Garcia-Martin, Ruben; Sprott, David; Klotzsche-von Ameln, Anne; Grossklaus, Sylvia; Mitroulis, Ioannis; Chavakis, Triantafyllos; Economopoulou, Matina (Thrombosis and Haemostasis, 2019)
The replication stress inflicted on retinal endothelial cells (ECs) in the context of hypoxia-induced pathological neovascularization during proliferative retinopathy is linked with activation of the deoxyribonucleic acid (DNA) repair response. Here, we studied the effect of deficiency of the DNA damage response adaptor 53BP1, which is an antagonist of homologous recombination (HR), in the context of proliferative retinopathy. In the model of retinopathy of prematurity (ROP), 53BP1-deficient mice displayed increased hypoxia-driven pathological neovascularization and tuft formation, accompanied by increased EC proliferation and reduced EC apoptosis, as compared with 53BP1-sufficient mice. In contrast, physiological retina angiogenesis was not affected by 53BP1 deficiency. Knockdown of 53BP1 in ECs in vitro also resulted in enhanced proliferation and reduced apoptosis of the cells under hypoxic conditions. Additionally, upon 53BP1 knockdown, ECs displayed increased HR rate in hypoxia. Consistently, treatment with an HR inhibitor reversed the hyper-proliferative angiogenic phenotype associated with 53BP1 deficiency in ROP. Thus, by unleashing HR, 53BP1 deletion increases pathological EC proliferation and neovascularization in the context of ROP. Our data shed light to a previously unknown interaction between the DNA repair response and pathological neovascularization in the retina.
Keywords: 53BP1; homologous recombination; angiogenesis; hypoxia; retinopathy; endothelium